Outcomes Among People With Schizophrenia Participating in General-Population Smoking Cessation Treatment: An Observational Study. (May 2023) - Veldhuizen, Scott; Behal, Anjali; Zawertailo, Laurie; Melamed, Osnat; Agarwal, Mahavir; Selby, Peter
Objective: People with schizophrenia are much more likely than others to smoke tobacco, raising risks of disease and premature mortality. These individuals are also less likely to quit successfully after treatment, but the few existing clinical and observational studies have been limited by small sample sizes, and have generally considered specialized treatment approaches. In this analysis, we examine outcomes, service use, and potential explanatory variables in a large sample of people with schizophrenia treated in a general-population cessation program. Method: Our sample comprised 3, 011 people with schizophrenia and 77, 790 controls receiving free nicotine replacement therapy through 400 clinics and health centres. We analysed self-reported 7-day abstinence or reduction at 6-month follow-up, as well as the number of visits attended and self-reported difficulties in quitting. We adjusted for demographic, socioeconomic, and health variables, and used multiple imputation to address missing data. Results: Abstinence was achieved by 16.2% (95% confidence interval [CI], 14.5% to 17.8%) of people with schizophrenia and 26.4% (95% CI, 26.0% to 26.7%) of others (absolute difference = 10.2%; 95% CI, 8.5% to 11.9%; P < 0.001). After adjustment, this difference was reduced to 7.3% (95% CI, 5.4% to 9.3%; P < 0.001). Reduction in use was reported by 11.8% (95% CI, 10.3% to 13.3%) and 12.5% (95% CI, 12.2% to 12.8%), respectively; this difference was nonsignificant after adjustment. People with schizophrenia attended more clinic visits (incidence rate ratio [IRR] = 1.15, 95% CI = 1.12% to 1.18%, P < 0.001) and reported more difficulties related to "being around other smokers" (odds ratio [OR] = 1.28; 95% CI, 1.11% to 1.47%; P = 0.001). Conclusion: There is abundant demand for tobacco cessation treatment in this population. Outcomes were substantially poorer for people with schizophrenia, and this difference was not explained by covariates. Cessation remained much better than for unaided quit attempts, however, and engagement was high, demonstrating that people with schizophrenia benefit from nonspecialized pharmacological treatment programs.